Employee engagement practices during COVID‐19 lockdown - Chanana, Nisha (J Public Aff, 2020)
In the present business situation during the COVID‐19 pandemic, employee engagement has become one of the utmost prominent primacies for human resource managers and practitioners in organizations due to lockdown. The paper is to determine the engagement of employees by various companies during coronavirus pandemic. Organizations nowadays are constantly developing innovative and effective means to engage the employees during this tough time. This paper is a conceptual paper that is based on various research papers, articles, blogs, online newspapers, and reports of World Health Organization. During this pandemic situation, organizations are evolving many engagement activities like online family engagement practices, virtual learning and development, online team building activities, webinars with industry experts, online conduct weekly alignment sessions, team meet‐ups over video conference for lunch, short online game sessions, virtual challenges and competitions, online courses, appreciation sessions, communication exercises, live sessions for new‐skill training, online counseling sessions, recognition and acknowledgment session, webinars dealing with anxiety and stress, providing online guidance for exercise and meditation, social interactions in a virtual office, classrooms training modules digitally, e‐learning modules, and many more creative learning sessions. Work‐from‐home regime engagement activities are very fruitful for employees as well as for organizations. Those organizations doing these kinds of engagement activities for their employees are learning new skills and developing themselves. Employees are feeling committed to the organization and stay motivated during this tough time of COVID‐19 pandemic.